PENERAPAN METODE EKSPERIMENTAL LEARNING PADA MATA KULIAH KONSERVASI TRADISIONAL - Tambak Sihno Purwanto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Low student engagement in learning is caused by the predominance of lecture-based teaching methods in the Art Conservation Study Program. This study addresses the following research question: how is the experiential method implemented in classroom activities, specifically in the case study of the Traditional Conservation Methods course in the Art Conservation Study Program, Faculty of Fine Arts and Design, Indonesian Institute of the Arts Yogyakarta? The study aims to analyze the implementation of the Experiential Learning approach in the Traditional Conservation Methods course at the Art Conservation Study Program, Faculty of Fine Arts and Design, Indonesian Institute of the Arts Yogyakarta. The research employed a Classroom Action Research design based on the Kurt Lewin model. The research subjects were students enrolled in the Traditional Conservation Methods class of the Art Conservation Study Program, Faculty of Fine Arts and Design, Indonesian Institute of the Arts Yogyakarta. The findings revealed that the implementation of experiential learning methods increased students’ interest in learning traditional conservation. Students were able to understand theoretical concepts through direct interaction with the phenomena being studied. In addition, students were capable of documenting traditional conservation practices within communities and presenting them again in an academic context. The research findings demonstrate that integrating experience with theory can bridge the gap between traditional practices and scientific approaches. Therefore, the experiential learning method has strong potential to be further developed as an effective learning method in art conservation education. ABSTRAK Rendahnya keterlibatan mahasiswa dalam pembelajaran karena kebanyakan metode pembelajaran di Prodi Konservasi Seni menggunakan metode ceramah. Pertanyaan dalam penelitian ini adalah, bagaimana metode eksperimental diterapkan pada kegiatan perkuliahan: studi kasus kuliah metode konservasi tradisional Program Studi Konservasi Seni Fakultas Seni Rupa dan Desain Institut Seni Indonesia Yogyakarta. Tujuannya menganalisis penerapan pendekatan Experiential Learning pada mata kuliah Metode Konservasi Tradisional Program Studi Konservasi Seni FSRD ISI Yogyakarta. Penelitian menggunakan desain Penelitian Tindakan Kelas model Kurt Lewin. Subjek penelitian adalah mahasiswa kelas metode konservasi tradisional Prodi Konservasi Seni FSRD ISI Yogyakarta. Hasil penelitian menunjukkan bahwa penerapan metode eksperimental learning meningkatkan minat mahasiswa dalam pembelajaran konservasi tradisional. Mahasiswa mampu memahami teori berkat pengalaman berinteraksi langsung dengan fenomena yang dipelajari. Mahasiswa mampu mendokumentasikan praktik konservasi tradisional di masyarakat dan mempresentasikan kembali secara akademis. Temuan penelitian memperlihatkan integrasi pengalaman dengan teori dapat menjembatani kesenjangan antara praktik tradisional dan pendekatan ilmiah. Dengan demikian, metode eksperimental learning berpotensi untuk dikembangkan sebagai metode pembelajaran konservasi seni.